Pemberdayaan Ekonomi Masyarakat Desa Negeri Tongging melalui Ekonomi Sirkular: Program Tukar Sampah & Ecobrick: Empowering the Economy of Negeri Tongging Village through Circular Economy: Waste Exchange Program & Ecobricks - Muhammad Fadli Brahmana; Siti Aisyah; Hasbi Fauzan Insyirah; Muhammad Yuga Syahputra; Farhan Abdillah Panjaitan (Lembaga Pengembangan Kinerja Dosen, 2026)
Plastic waste management in rural areas, particularly in tourism villages, remains an environmental challenge that requires sustainable solutions. Negeri Tongging Village, as a tourism area around Lake Toba, has experienced an increase in household plastic waste that has not been managed optimally, potentially affecting environmental quality and community well-being. This community service activity aimed to enhance community awareness and capacity in plastic waste management through the implementation of a circular economy approach based on a waste exchange program and ecobrick production. A participatory approach was employed by actively involving the community in all stages of the activity, including socialization, program implementation, and evaluation. The program was carried out during the 2025 Community Service Program of Universitas Islam Negeri Sumatera Utara, consisting of circular economy socialization, collection of plastic waste through an exchange scheme with basic necessities, training on ecobrick production, and the provision of supporting facilities for environmental cleanliness. The results indicate an increase in community participation and environmental awareness, a reduction in improperly disposed plastic waste, and an improvement in community skills in processing plastic waste into useful products. In addition, the activity strengthened mutual cooperation and environmental responsibility among community members. In conclusion, the application of a circular economy approach through ecobrick-based activities can serve as an effective alternative solution for plastic waste management while simultaneously supporting sustainable community empowerment in rural tourism areas.